Analysis of female athlete triad in adolescent female Bharatanatyam dancer using low energy availability questionnaire - Tambe, Sharayu S.; Puntambekar, Anjali S. (International Journal Of Community Medicine And Public Health, 2021)
Background: The aim of this study was to assess adolescent Bharatanatyam female dancers for female athlete triad (FAT) which includes low energy availability (LEA), musculoskeletal injury profile, gastrointestinal function and menstrual dysfunction using in females LEAF questionnaire. Methods: The approval was taken from the institutional review board of K. J. Somaiya college of physiotherapy. A pre-designed, pre-validated, questionnaire was distributed in the google form layout, among population according to the inclusion and exclusion criteria; asking for consent to confirm their willingness to participate voluntarily. After confirmation, the participants were directed to complete the LEAF questionnaire, maintaining their confidentiality. Data collected was analyzed using descriptive statistics. Results: A total of 82 participants took part in this study. The cumulative incidence of musculoskeletal injuries is about 50%. 35.4% of population experienced gaseous or bloated abdomen apart from menstrual function and 32.9% experienced cramps or stomach ache which were not related to menses. 7.3% of population reported primary amenorrhea, 35.8% reported secondary amenorrhea and 18.6% reported oligomenorrhea. Thus, overall, 34.5% population reported all the components of FAT. Conclusions: Prevalence of LEA in Bharatanatyam female dancers was reported amongst which prevalence of musculoskeletal injuries was high amongst the participants followed by menstrual dysfunction. LEA might have been interpreted as a usual or needed procedure to achieve better performance in past, but now it is recognized that it may lead to several negative consequences. Therefore, timely screening of dancers along with adequate training protocol will help alleviate LEA.